Detection of four rare thalassemia variants using Single-molecule realtime sequencing - Luo, Shiqiang; Chen, Xingyuan; Zeng, Dingyuan; Tang, Ning; Yuan, Dejian; Liu, Bailing; Chen, Lizhu; Zhong, Qingyan; Li, Jiaqi; Liu, Yinyin; Chen, Jianping; Wang, Xiaoyuan; et al. (Frontiers in Genetics, 2022)
Conventional methods for the diagnosis of thalassemia include gap polymerase chain reaction (Gap-PCR), reverse membrane hybridization (RDB), multiplex ligation dependent probe amplification (MLPA) and Sanger sequencing. In this study, we used single molecule real-time technology (SMRT) sequencing and discovered four rare variants that have not been identified by conventional diagnostic methods for thalassemia. We also performed genotype and phenotype analyses on family members of thalassemia patients. The SMRT technology detected five cases in which the proband had abnormal results by conventional diagnostic methods or inconsistencies between the genotype and phenotype. The variants included two cases of an α-globin gene cluster 27,311 bp deletion, –27.3/αα (hg38 chr16:158664-185974), one case of an HS 40 region 16,079 bp deletion (hg38 chr16:100600-116678), one case of a rearrangement of α3.7α1α2 on one allele and one case of a β-globin gene cluster HBG1-HBG2 4,924 bp deletion (hg38 chr11:5249345-5254268). This study clarified the hematological phenotypes of four rare variants and indicated the application value of SMRT in the diagnosis of rare α-globin and β-globin gene cluster deletions, gene recombination and deletion breakpoints. The SMRT method is a comprehensive one-step technology for the genetic diagnosis of thalassemia and is particularly suitable for the diagnosis of thalassemia with rare deletions or genetic recombination.